Retaining international students for advanced degree in Malaysia: quality matters - Foo, Chuan Chew; Russayani Ismail; Lim, Hock Eam (Penerbit Universiti Kebangsaan Malaysia, 2016)
As the world is becoming more globalised, cross border education continues to preoccupy the agenda of internationalisation of higher education with more and more countries participating as education providers. Competition for students requires the education providers to step-up in their quality assurance and governance as to ensure their sustainability in years to come. The shift of intention from merely focusing on internationalisation as a source of revenue generation to a more diverse objective of talent development that promotes research and innovation is imperative. Thus, the ability of the host countries to attract high quality students and retain them for further degree is nevertheless essential. Despite huge literature concentrating on identifying the factors that can attract potential international students to enrol in host countries, few known studies have been carried out to identify the factors that are able to influence the choice of the currently enrolled international students to remain in Malaysia for their further degrees. Using the data of 753 international students, gathered from a sample of few universities in Malaysia, this particular study employs a Logit Model in an attempt to identify the educational choice motives that influence the decision of the currently enrolled international students to remain in Malaysia for their higher level of study. The finding shows that the consumption motive dominates the investment motive, suggesting that students’ decision to remain in Malaysia for further degree is highly related to the consumption motive as compared to the investment motive. A comfortable study environment, high quality services and facilities, excellent faculty members and easy access to information regarding matters related to education in Malaysia significantly influence the students’ decision to stay to further their studies. The findings from this study lend support to a commonly held view that the quality of education matters.